472Long-term effectiveness of 3-dose primary course and 4-year booster dose of pertussis vaccine in Australia. (2nd September 2021) - Jayasundara, Duleepa; Sheridan, Sarah; Randall, Deborah; Campbell, Patricia; Edmond, Karen; Liu, Bette; McIntyre, Peter B; Gidding, Heather F; Wood, James G
Abstract: Background: Australia's National Immunisation Program recommended a 3-dose primary Diphtheria-Tetanus-Pertussis (DTP) vaccination course at 2, 4 and 6 months and a booster dose at 4 years during 2003-2015. We examined vaccine effectiveness by time since doses 3 and 4, as studies to date have shown conflicting results. Methods: Perinatal, immunisation, pertussis notification and death data were linked for 1, 086, 319 infants born in two Australian states in 2003-2012. Administration of DTP doses 3 and 4 from 5.5-7 months and 47-53 months respectively, was considered age-appropriate. Adjusted Cox proportional hazards models with time-varying vaccination status were used to estimate vaccine effectiveness (VE = 1–hazard ratio) against notified pertussis post age-appropriate doses 3 and 4 compared to unvaccinated children, with additional benefit of dose 4 compared to receipt of primary course alone. Results: Dose 3 VE declined from 79% (CI 75%-83%) from 0-6 months to 64% (CI 60%-67%) at 6-36 months and 45% (CI 31%-56%) at 36-42 months post-vaccination. Compared to unvaccinated children, VE after dose 4 declined from 83% (CI 80%-86%) at 0-12 months to 67% (CI 60%-72%) and 55% (CI 46%-63%) in the following two 12-month periods post-vaccination. When compared to dose 3, the relative VE for dose 4 was 58% (CI 51%-64%) in 0-18 months post-vaccination. Conclusion and Key messages: Our study adds to previous Australian evidence for substantial waning of vaccine induced immunity against pertussis over a 3-year period following dose 3. VE was significantly higher in the 18 months following dose 4 compared to receipt of primary course alone.